Using pathchar to estimate Internet link characteristics. - Downey, Allen B. (Computer communication review.)
We evaluate pathchar, a tool that infers the characteristics of links along an Internet path (latency, bandwidth, queue delays). Looking at two example paths, we identify circumstances where pathchar is likely to succeed, and develop techniques to improve the accuracy of pathchar's estimates and reduce the time it takes to generate them. The most successful of these techniques is a form of adaptive data collection that reduces the number of measurements pathchar needs by more than 90% for some links.